Discontinuing analyst coverage due to resource reallocation: Euphemism for unfavorable firm outlook? - Charitou, Andreas; Karamanou, Irene; Kopita, Anastasia (My University, 2025)
Following the SRO rulings' requirement that analysts announce coverage terminations including either their final rating or the reason for the termination, we find 86.7 % of the voluntary terminations being attributed to ‘resources’ reallocation’ and only 13.3 % to firm poor outlook. Developing a classification algorithm to split the reallocation terminations into performance-based terminations (those driven by the dropped firm's poor outlook) and resource-constrained terminations (those unrelated to firm performance), we show that although the market's reaction to the termination announcement does not differ between the two sub-samples, future returns and financial performance of the performance-based sample significantly underperform those of the resource-constrained sample. We perform a number of additional analyses, including the use of terminations explicitly attributed to firm bleak output, to ex ante differentiate between the two types of reallocation terminations. We conclude that analysts withhold unfavorable news through the provision of news-neutral reasonings, in contrast to the regulators' intentions.
Keywords: Analyst coverage terminations; Financial analysts; SRO rulings; Termination announcements; Long-run firm performance